Exploring health professionals' understanding of evidence‐based treatment for idiopathic toe walking. (30th January 2020) - Williams, Cylie M.; Gray, Kelly; Davies, Nina; Barkocy, Marybeth; Fahey, Michael; Simmonds, Jane; Accardo, Pasquale; Eastwood, Deborah; Pacey, Verity
Abstract: Background: Idiopathic toe walking (ITW) is an exclusionary diagnosis resulting in a child walking on the balls of their feet. Preferred treatment options may be due to the severity of the toe or the health professional preference There are limited guidelines supporting consistent treatment recommendations for this condition. This research aimed to understand agreement between health professionals' knowledge of evidence for common treatment strategies for ITW and if health professionals supported these strategies being used in clinical practice. Methods: An international online survey was opened to registered health professionals who treat children with ITW between July 2017 and March 2018. The survey had two components: (a) demographic variables and variables relating to knowledge of evidence about ITW treatments and (b) support for common treatment strategies. Additional data on strategy use, referrals, and preference were collected. Kappa statistics described intra‐rater agreement between evidence knowledge and support. Multivariable regression analyses identified factors associated with the 10 most commonly preferred treatments. Results: There were 908 international responses. Kappa agreement for paired correct responses determined a fair agreement for evidence support knowledge for four strategies including watch and wait (Kappa = 0.24), stretching (Kappa = 0.30), sensory integration strategies (Kappa = 0.40), and motor control strategies (Kappa = 0.24) and moderate responses for 13 others. No strategies had greater than moderate agreement between correct knowledge of evidence and strategy support. Profession, location, number of children seen in practice, and not correctly identifying the evidence factored into many of the most commonly used strategies for ITW ( p < .05). Conclusions: The results from this study, which confirm a variety of interventions, are utilized in the management of ITW around the world. Furthermore, there remains a disconnection between paediatric health professionals' understanding of the evidence of common treatment strategies of ITW and a consensus for the treatment of this condition.